e-ASPECTS derived acute ischemic volumes on non-contrast-enhanced computed tomography images - Nagel, Simon; Joly, Olivier; Pfaff, Johannes; Papanagiotou, Panagiotis; Fassbender, Klaus; Reith, Wolfgang; Möhlenbruch, Markus Alfred; Herweh, Christian; Grunwald, Iris Q. (International journal of stroke, 2020)
Background and purpose Validation of automatically derived acute ischemic volumes (AAIV) from e-ASPECTS on non-contrast computed tomography (NCCT). Materials an...
September 30, 2019
Gesehen am 10.11.2020